Vitamin B complex: B group vitamins and their role in the body - Zubeyde Bayram-Weston (Nursing Times, 2024)
Vitamin B complex plays a vital role in cellular metabolism and is discussed in this second article in a series on vitamins and minerals. A deficiency in B group vitamins can hamper efficient energy production in cells, leading to adverse health effects. Deficiency of vitamin B1, common in people with alcohol use disorder or AIDS, can cause beriberi, which affects the nervous system and heart. Vitamin B3 deficiency leads to pellagra, characterised by dermatitis, diarrhoea, depression and dementia. Deficiencies in vitamins B9 (folate) and B12 can lead to anaemia and neurological issues.